Article 10 of the European Convention on Human Rights from the perspective of regional newspapers’ freedom of expression in Latvia - Pole, Kristiāna (Riga Graduate School of Law, 2018)
The present thesis raises a question: are media able to fulfill its “watchdog” role and spread democracy and freedom of expression in Latvia? Is society informed about unfair Municipality’s practice to portray itself in a flattering light by generating media content and restricting journalists’ rights guaranteed under Article 10 of the European Convention on Human Rights? Media monopolisation and state’s interference with journalists’ freedom of expression are unambiguously prohibited therefore situations when violations of their rights take place should be avoided. However, personally inquired Latvian media representatives prove the opposite: due to favourable conditions for interpretation of Latvian legislation and missing elements in the Municipality’s regulations in general, violations of press freedom especially in Regional newspapers occur.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Freedom of expression; Latvia